Geological Characteristics of the Mesozoic Unconformities in Eastern Heilongjiang, NE China: Implications for the Mesozoic Continental Margin Evolution of Northeast Asia - Zhao, Xueqin; Lv, Congcong; Jiang, Yaoxi; Zhu, Heyan; Wang, Fudong; Chai, Peiran (Frontiers in Earth Science, 2022)
Most of the significant petroleum- and coal-bearing sedimentary basins in Northeast Asia originated via rifting and thermal subsidence during the Late Jurassic-Early Cretaceous, followed by basin inversion in the Late Cretaceous. However, the tectonic background governing these basin prototype shifts has not been fully explored. The unconformities are excellent archives of plate boundary interactions and geodynamic switches in subduction zones. The Eastern Heilongjiang Province (EHLJ), Northeast China (NE China), comprises a series of Mesozoic-Cenozoic residual basins with well-preserved successions and provides significant insights into the tectonic characteristics and background of Northeast Asia. Mesozoic unconformities and large-scale contractional structures in the basins mark a series of important tectonic transitions in Northeast Asia. Based on the synthesis information of regional Mesozoic unconformities identified in the seismic reflection profiles and field outcrops of EHLJ, the tectonic characteristics and geodynamic background of the Mesozoic continental margin basins in Northeast Asia are analysed. The Middle-Upper Jurassic/basement unconformity (U1) can only be found in some areas of the Sanjiang and Hulin basins. It was a response to the continental collision of Siberia and the northern China–Mongolia tract along the Mongolia–Okhotsk suture during the Jurassic. The Paleo-Pacific Plate rapidly subducted in the NNW direction towards the eastern margin of Eurasia in the early Lower Cretaceous resulting in a mass of strike-slip faults and the widespread absence of deposits (Valanginian) (U2) in the EHLJ. Because of the subduction slab rollback of the Paleo-Pacific Plate during the late Lower Cretaceous, the local asthenospheric material upwelled, and fault and volcanic activities intensified in Northeast Asia. The Lower Cretaceous Dongshan Formation (Fm)/Muleng Fm unconformity (U3-1) reflects a specific scale of bimodal magmatism in the Songliao Basin and the EHLJ. The Pacific Plate subducted in a transformation from NNW to WNW during the early Upper Cretaceous (Cenomanian). The Houshigou Fm (Qixinhe Fm)/Lower Cretaceous angular unconformity (U3) reflects that on the basins experienced denudation after being extensively uplifted from the subduction events. With the subduction of the Kula Plate, a compression stress field during the later Upper Cretaceous Period controlled NE China. The basins underwent a widely compressive deformation, accompanied by large-scale thrusts, denudation and deplanation, resulting in Paleogene/Cretaceous unconformity (U4) was formed.